Endometrial stromal tumor with whorling and GREB1::CTNNB1 fusion-a case report on a rare entity - Kendall Bártů, Michaela; Flídrová, Miroslava; Němejcová, Kristýna; Hojný, Jan; Dvořák, Jiří; Michalová, Květoslava; Dundr, Pavel (Virchows Archiv, 2025)
Endometrial stromal tumors are rare lesions with a diverse morphology, which may make achieving the correct diagnosis challenging in some cases. We report a case of a uterine mesenchymal tumor diagnosed as endometrial stromal nodule with a peculiar whorled morphology and GREB1::CTNNB1 fusion confirmed by transcriptome RNA sequencing. The tumor was sharply demarcated, lacked invasive growth, and had benign behavior, as the patient remained without disease recurrence 15 years later. Immunohistochemically, the tumor cells showed diffuse nuclear expression of beta-catenin, confirming the activation of the beta-catenin pathway. Our case represents only the 4th reported case of CTNNB1-rearranged endometrial stromal tumor with extensive whorling. The biological nature of uterine tumors characterized by whorled morphology and rearrangement of CTNNB1 is not yet clear, which underscores the importance of genetic profiling for accurate diagnosis and potential targeted therapies in malignant cases.
Keywords: Neoplasm Proteins; nádorové proteiny; endometriální stromální nádory; Middle Aged; GREB1::CTNNB1 fusion; Uterine mesenchymal tumors; GREB1; Endometrial stromal tumors; nádory endometria; beta Catenin; Endometrial Neoplasms; Gene Fusion; Biomarkers, Tumor; Endometrial Stromal Tumors; ženské pohlaví; nádorové biomarkery; Humans; lidé středního věku; fúze genů; ESN; Female; beta-katenin; lidé